Implantación del sistema de contabilidad comercial y aplicación de indicadores en la “Ferretería PQ” de la ciudad de Cuenca, periodo julio a septiembre del 2014 - Ulloa Bustos, Silvia Alexandra (2015)
This thesis research "COMMERCIAL SYSTEM IMPLEMENTATION OF ACCOUNTING AND APPLICATION OF INDICATORS IN THE" HARDWARE PQ "BASIN CITY, PERIOD JULY TO SEPTEMBER 2014"; was raised in order to develop practical application of the appropriate accounting system for a commercial company whose activity to date there has expert advice, according to the rules and techniques of applying a set Accounting Organization Accounting Principles Generally Accepted and other legal norms and laws. Also was developed in consideration of the Rules of Academic System of the National University of Loja, previous to choose the degree of Engineer in Accounting and Auditing Public Accountant. The objectives in the Hardware "PQ" were made to make the accounting process that begins with the initial inventory; a plan and manual accounts according to financial turnover of the company was prepared; State Initial situation was determined; proceeded with the recording of transactions in the journal; the respective ledgers, trial balance and worksheet for the Financial Statements, the qualifying documents could establish the respective financial analysis at the end of the period set was generated. Upon completion of the work has a commercial accounting system adapted to the Hardware "PQ", with books of original entry and Financial Statements; is recommended to continue running so that the business owner can have economic and financial information in a timely manner, to facilitate decision-making